The development of green finance under the goal of carbon neutrality: A review from China’s perspective - Xue, Yawei; Ma, Tianli; Zhuang, Tianyuan; Ma, Yingying (Frontiers in Earth Science, 2023)
Extreme environmental and climate problems have been ravaging the world, causing serious economic losses and hindering human development, so that carbon neutrality has become a global undertaking related to the survival of human civilization. To ensure climate change mitigation and carbon emission reduction, this paper finds that green finance as an important and efficient tool has become a legislative priority for many countries and have been embedded in the path to achieve carbon neutrality. On the basis of in-depth analysis of the evolution and development of global green finance, this paper reviews and summarizes the development of green finance in China through literature analysis and horizontal comparison, and explores concrete recommendations and feasible tools that can be tailored to China’s carbon neutrality goal and stage of development. It is concluded that China needs to improve the green finance operation mechanism and flexible policy framework, to formulate a more accurate timetable and roadmap, to strengthen the modernization of the governance system and governance capacity and to promote the global green finance cooperation.